Fire, boycott, threat and harm: social and political violence within the local community. A study of three Munster counties during the Irish Civil War, 1922-23. - Clark, G; Gemma Clark (2011)
In its investigation of social and political violence during the Irish Civil War, this thesis tackles the diverse range of deliberate, frightening and harmful actions—largely neglected by military and political histories of the conflict—that surfaced in local communities in Ireland during 1922–23. Through a three-county study of Limerick, Tipperary and Waterford, in the province of Munster, this thesis examines and explains violence perpetrated alongside and away from armed encounters between the anti-Treaty republican army and Free State forces. It identifies three main categories of violence: arson (the burning of houses, crops and infrastructure), intimidation (including boycott, damage to property, verbal and written threats, animal maiming, cattle driving and land seizure) and violence against the person (bodily damage or death through physical contact or the use of weapons). The thesis charts, where possible, the frequency of the violent act and, in exploring the symbolism and strategies involved in arson, intimidation and violence against the person, identifies two key functions of social and political violence. For one, targeted violence was used, during the Irish Civil War, to regulate community relations: state-sanctioned ethnic cleansing did not take place, but the religious and political minority (Protestants, ex-Servicemen and other British Loyalists) were deliberately persecuted, resulting in their flight from Munster. Land is another powerful motif in the thesis; the second key function of violence was to challenge attitudes towards rural issues and force redistribution outside the official channels. The thesis also places the Irish Civil War in perspective: the prolific bloodshed, sexual violence and gruesome torture witnessed in Central Europe, after World War I, did not become the norm in Ireland. Animals and private property bore the brunt of the severest actions in the three Munster counties. By bringing to light victims’ experiences of violence recorded in largely unexplored compensation claims, this thesis captures the complex questions of loyalty and identity—facing armed actors and officials, as well as civilians—that beset the violent and chaotic establishment of independent Ireland.